Experimental study of seepage and water-rock heat transfer in granite fracture under chemical action - Ruotao Liu; Guan Rong; Bowen Li; Zhongjie Yu; Huqi Zhang; Qinyan Qiu (European Journal of Environmental and Civil Engineering, 2026)

High-yield hydrogen production via dolomite/ilmenite synergistic catalytic gasification in a fluidized bed reactor - Shaosheng Fang; Panting Li; Dongfang Li; Shaoxiang Pu; Rong Yang; Aoyang Zhang; Xing Zhu; Hairui Yang; Man Zhang; Hua Wang (Fuel, 2026)

Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Coordinating carbon trading and green certificates for low-carbon cross-regional electricity transmission: Evidence from Inner Mongolia, China - Xin Zhang; Boyi Li; Richao Cong; Toru Matsumoto; Rong-Gang Cong (Energy and Climate Change, 2026)

Exploring the potential mechanisms of the Prunus mume-Prunella vulgaris herb pair in treating endometrial polyps based on network pharmacology and molecular docking - Wen Yan Zhang; Yuan Yuan; Li Fan; Guang Rong Huang; Shu Yu Pan; Jing Xiao (Molecular Genetics and Genomics, 2026)

Correction to: Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

Gsα deficiency in macrophages promotes tumor progression via the MAPK signaling pathway - Wenjiang Yan; Jingjing Yang; Siyu Tan; Tixiao Wang; Rong Xiao; Na Li; Min Chen; Lee S. Weinstein; Lifan He; Chang Ma; Jingsu Zhang; Lifen Gao; et al. (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

DA-MOT: a directed-angle-aware multi-object tracking framework for dairy cows - Tonghui Wu; Rong Wang; Haiyan Song; Zhiyong Zhang; Qifeng Li; Zhaoyang Wang; Yan Shi; Ronghua Gao (Computers and Electronics in Agriculture, 2026)

First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

From descriptive digital twins to closed-loop intelligent agents: Adaptive biogeochemical management in river-reservoir systems - Honghong Guo; Ruopu Yuan; Tongtong Wang; Rong Li; Yijia Li; Yuhang Su; Haihan Zhang; Tinglin Huang (Water Research, 2026)

Assessments of gully erosion susceptibility in typical thick-layer Mollisol region of Northeast China - Binglong Wu; Fenli Zheng; Ximeng Xu; Yucheng Fu; Dennis C. Flanagan; Rong Li; Jiaqiong Zhang; Bin Wang; Jinxia Fu (Soil and Tillage Research, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Systematic identification pepper CaE2F transcription factor reveals the role of CaDPb in drought stress response - Rong Lu; Yishui Chen; Longxue Li; Zilin Zhang; Qinghong Zhou; Meixia Wang; Huibin Han (Plant Science, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Multi-omics analysis reveals coordinated epigenetic dysregulation in atrazine-induced dopaminergic neurotoxicity - Shuohan Ning; Zheng Liu; Yanshu Li; Rong Zhang (Food and Chemical Toxicology, 2026)

Co-N4 anchored porphyrin-based COFs enable sacrificial-agent-free photocatalytic extraction of dispersed uranium resources - Chongheng Li; Jinjiao Pan; Yue Ma; Huazhen Rong; Yilei Zhang; Zhuoming Yang; Yifei Zhou; Chuan Gan; Yihui Yuan; Ning Wang (Desalination, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

AIE-active dual-pore covalent organic framework for colorimetric/fluorescence detection and degradation of perfluorooctanoic acid - Tianyuan Yu; Shuai Liu; Shaoxi He; Guoyi Pu; Xi Zhang; Yanxiong Liu; Wenyu He; Ziyu Bao; Zezhou Zhao; Jiahui Liu; Fei Li; Rong Sheng Li; et al. (Chemical Engineering Journal, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Artificial womb technology: Progress, challenges, and future directions toward extrauterine gestation - Di Mao; Bingkai Su; Shujie Zhang; Jizhou Li; Lei Zhang; Xunsi Qin; Rong Li (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Carbon cloth-mediated direct interspecies electron transfer effect on the intensification mechanism of high-load codigestion dynamic membrane bioreactors - Bao-Shan Xing; Yi-Fan Wu; Yi Zhang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Multi-copy expression of classical swine fever virus E2 in a recombinant pseudorabies virus enhances immunogenicity and supports its potential as a PRV-CSFV bivalent vaccine candidate - Xianfei Shang; Hui Zhao; Yufeng He; Zhenxiang Rong; Xiquan Ke; Jinglei Gao; Ke Zhang; Jiyuan Luo; Min Zhang; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Secondary forest succession shifts soil carbon priming from microbial to mineral control through dynamic microbe–mineral coupling - Panpan Wu; Jing Zhang; Xi'an Cai; Zhijian Mou; Yue Li; Wenjia Wu; Tengteng Li; Rong Mao; Zhanfeng Liu (Soil Biology and Biochemistry, 2026)

DNA methylome analysis reveals EjABCG23-mediated epigenetic regulation underlying fruit russeting in white-fleshed loquat - Kun Zhang; Yuying Ding; Rong Su; Chang Liu; Xuelian Li; Yang Wang; Yan Deng; Qiong Zhou; Xiaojun Chen; Yuxing Li; Qunxian Deng (Postharvest Biology and Technology, 2026)

Glacial pacing and monsoon modulation of multi-scale lacustrine carbon sequestration in the Weihe Basin, North China - Yili Long; Xiaoqing Rong; Hang Zhang; Hai Xu; Yougui Song; Hong Chang; Xiaoke Qiang; Li Ai; Xingxing Liu; Youbin Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

The needs-solution-prototype-validation model: A feasibility study of nurse-led interdisciplinary collaboration in medical device innovation - Xiaodong Zhang; Fengli Wang; Aiying Gu; Haoyuan Li; Wei Wang; Yongchao Huo; Rong Xu; Yuanfeng Xue; Guohong Li; Yan Geng (Next Research, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Anomalously low winter sea surface temperatures during the holocene thermal maximum: A novel proxy from the Northern South China Sea - Yiping Yang; Rong Xiang; Fuchang Zhong; Lanlan Zhang; Sui Wan; Wubiao Li (Global and Planetary Change, 2026)

Spatial patterns and interspecific associations of Pinus kesiya and its main companion species in a natural forest, southwestern China - Liyuan Zhang; Rong Tang; Xiaobo Huang; Xinyu Li; Yuanyuan Yi; Shao Lei; Jianrong Su; Shuaifeng Li (Forest Ecology and Management, 2026)

Reliable quantification and efficient purification of osteopontin from bovine milk using anion-exchange and membrane chromatography - Xinru Zuo; Shuai Ren; Jinrui Du; Yimeng Li; Muran Ma; Lu Tao; Yinzi Cui; Rong Fan; Yuhong Mao; Guoqiang Chen; Caiyun Wang; Yinhua Wan; et al. (Food Chemistry, 2026)

Addressing fruit allergen detection gaps: A validated LC-MS/MS method for eight allergenic fruits in foods - Yingnan Shencheng; Meizhen Zhou; Yumeng Zhao; Siyi Li; Yutong Xu; Yanan Gao; Xiaoxue Jia; Min Gao; Rong Zhang; Shuyan Liu; Feng Ye; Ya Zhang; et al. (Food Chemistry, 2026)

Reducing the residual oil body content in soy protein isolate (SPI) through pH regulation and studying the changes in physicochemical, flavor profiles, and processing properties - Merga Nagassa; Shudong He; Shuyun Liu; Yulong Deng; Huimei Li; Rong Zhang; Jiazhen Song; Suwei Jiang; Hanju Sun (Food Chemistry, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

Rapid in-situ recovery of starved anammox consortia: Metabolic stimulation and microbial synergy driven by organics and oxygen - Yihao Qiu; Chenrong Gu; Jiaqi Han; Jiaqi Zhang; Qi Zhang; Rong Li; Xiao-Ming Ji (Environmental Research, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Ecological restoration of coastal wetlands shapes soil carbon pools and microbial carbon cycling functions in Bohai Bay, China - Mengtuo Wen; Qiulan Zhang; Yasong Li; Jing Rong; Shengwei Cao; Yaci Liu (Estuarine, Coastal and Shelf Science, 2026)

Dynamic modeling and numerical simulation of dense particle multiphase flows in resonant acoustic mixing - Jingming Zhang; Mingming Shi; Bao Rong; Gouping Wang; Da Li; Xiaoting Rui (Chemical Engineering Journal, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

The microalgae-bacteria symbiotic inoculation enhances sandy soil multifunctionality and wind erosion resistance through microbial network reorganization - Lianhao Sun; Xin Sun; Haonan Zhang; Hui Nie; Chong Li; Xin Liu; Haidong Li; Xiongfei Zhang; Qianqian Liu; Jingyi Zeng; Weiqi Meng; Guoshuai Hou; et al. (CATENA, 2026)

Anaerobic digestion of recalcitrant organics and emerging contaminants in pharmaceutical wastewater for carbon neutrality and bioresource recovery: A critical review - Xinru Niu; Tao Zhang; Yao Xu; Jiaxin Ou; Chengzhen Meng; Fan Li; Lan Tang; Yong Hu; Chao Rong; Dapeng Li; Zhe Kong (Bioresource Technology, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Temporal trends in toxicities and major drivers of polycyclic aromatic hydrocarbon emissions in China from 1960 to 2019 - Xiao Yun; Huizhong Shen; Jin Li; Yuanzheng Zhang; Shuxiu Zheng; Rong Dai; Jinghang Wang; Haoran Xu; Wenxiao Zhang; Guofeng Shen; Jianmin Ma; Shu Tao (Atmospheric Environment, 2026)

α-Ketoglutarate attenuates ammonium chloride-induced ferroptosis by maintaining mitochondrial homeostasis in grass carp (Ctenopharyngodon idellus) hepatocytes - Yuling Zhang; Chengchen Jiang; Dapeng Li; Rong Tang (Aquatic Toxicology, 2026)

Semiconducting polymer-based ratiometric fluorescent nanoprobe for highly accurate imaging of H2S in inflammatory and tumor cells - Chen Han; Xing Wang; Yating He; Rong Wang; Hong-Min Meng; Lin Zhang; Zhaohui Li (Analytica Chimica Acta, 2026)

Enzymatic Preparation of Ejiao (Colla Corii Asini) Peptides and Their Preliminary Mechanism of Melanogenesis Inhibition - Xichao Fu; Shangwei Guo; Meijin Li; Zhijie Chen; Dan Liu; Cuicui Men; Na Yang; Xiaobo Duan; Xiaolu Tang; Yaru Zhang; Haibin Liu; Minghao Liu; et al. (International Journal of Peptide Research and Therapeutics, 2026)

Decadal Resampling Reveals Widespread Increases in Soil Microbial Diversity Associated With Nitrogen Deposition - Yi Fan; Yiheng Tao; Bin Hua; Paul Kardol; Yakov Kuzyakov; Shuang Pang; Yi Wu; Tingling Li; Wei Yang; Honghui Wu; Anton A. Goncharov; Anastasia Yu. Korotkevich; et al. (Global Change Biology, 2026)
Simulated manipulation experiments, such as nitrogen addition to mimic atmospheric nitrogen deposition, are widely used in global change research. However, experimental manipulations may differ from real‐world environmental change in their intensity, duration, and co‐occurrence, leaving long‐term changes in soil microbial communities and soil health insufficiently understood. To address this gap, we resampled soils from 38 forest and grassland ecosystems across eastern China in 2009 and 2019 and assessed microbial taxonomic and functional diversity using shotgun metagenomics. Microbial diversity increased by 17% over the decade, accompanied by clear shifts in community composition. Among the environmental variables considered, nitrogen deposition (~19 kg nitrogen ha −1 year −1 across ecosystems) was the strongest predictor of changes in seven of 12 microbial community metrics. Larger nitrogen deposition was also associated with increased relative abundances of nitrogen‐cycling genes and reduced spatial turnover in microbial community composition. These effects were consistent with a potential alleviation of nitrogen limitation and weakening of deterministic community assembly, although these mechanisms could not be directly established. In addition, increases in genes associated with carbon degradation and phosphorus cycling, together with declines in the relative abundances of pathogens, antibiotic resistance genes, and DNA viruses, coincided with the raise of the composite soil health index. Our findings demonstrate widespread decadal increases in soil microbial diversity and soil health across eastern China, with nitrogen deposition emerging as their strongest environmental factor. These results highlight that microbial responses to long‐term ambient environmental change can differ markedly from responses inferred from short‐term or high‐intensity manipulation experiments.

A robot herding strategy combining CMFF and MPC for shepherding - Hongbo Liu; Ping Song; Gang Liu; Xiaoping Xin; Yuping Rong; Luyu Ding; Junyao Gao; Zhuoming Wang; Yinglong Zhang; Pengzhen Li (Computers and Electronics in Agriculture, 2026)

An approach to predict methane emissions from pig housing by developing surrogated models of mass transfer coefficient and methane concentration at slurry surface - Chenglong Wang; Guoqiang Zhang; Chao Zong; Li Rong (Biosystems Engineering, 2026)

Plant litter enhances hexabromocyclododecane removal in riparian zones at high water level: Insights from the coupling of microbial dehalogenation and carbon cycling - Rong Wang; Juan Chen; Li Wang; Han Gao; Qihao Nie; Shunqing Zhang; Qiming He (Water Research, 2026)

Corrigendum to “Plasma-enhanced microbial electrolytic disinfection: Decoupling electro- and plasma-chemistry in plasma-electrolyzed oxidizing water using ion-exchange membranes” [Water Research, 225(2022), 119174] - Jiao Lin; Jishen Zhang; Renwu Zhou; Li Guo; Dingxin Liu; Mingzhe Rong; Michael G Kong; Kostya Ostrikov (Water Research, 2026)

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Surface interception and transport of 14C-labeled polystyrene nanoplastics by benthic marine organisms - Wenwen Song; Dongxu Li; Jun Zhang; Ziyun Huang; Hongjie Zhang; Changhong Liu; Aijun Miao; Yu Su; Rong Ji (Marine Environmental Research, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Role of macrophage NLRP3 inflammasome activation in real-ambient particulate matter-induced abnormal hepatic glucose metabolism - Dong Wu; Zhen Zhang; Sixin Chen; Haoran Chen; Daochuan Li; Shuxin Zhang; Junjie Dou; Yuanyuan Ma; Rong Zhang; Lianhua Cui (Journal of Environmental Sciences, 2026)

Dynamic failure mechanism and wave propagation characteristics of rock with double-layer filled joints - Yanzhe Li; Chuanxin Rong; Runze Zhang; Yang Wang (Geomechanics for Energy and the Environment, 2026)

Peptidomics-driven screening of ACE inhibitory peptides from cheese: Molecular mechanisms and modulation of endothelial function in HUVECs - Ying Xu; Dongyang Li; Huan Wang; Yu Zhang; Liangyan Rong; Ruren Li (Food Bioscience, 2026)

Co-removal of norfloxacin and Cr(VI) by Co/N-doped carbon activating peroxymonosulfate: 1O2 oxidation coupled with interfacial electron transfer - Yaru Li; Heming Wang; Rong Qiao; Dongxu Zhou; Fuyun Deng; Gaoyang Chen; Peixin Mao; Chaolin Yang; Xiaodong Zhang (Environmental Research, 2026)

Denitrification-enhanced anaerobic digestion for stable synergy of hydrolysis and methanogenesis of N, N-dimethylformamide by nitrate addition: Delayed stimulation effect for successful enrichment of functional microorganisms - Junjie Zhou; Zhihao Shi; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; Zhe Kong (Environmental Research, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

An inflammation-targeted hydrogel for the synergistic treatment of colorectal cancer and associated neuropsychiatric dysfunction - Keying Chen; Na Li; Anni Ren; Lingling Yang; Pei Xie; Yong Gao; Yanwu Li; Ying Tang; Rong Zhang; Huafeng Pan; Bangjiang Fang; Tongkai Chen; et al. (Chemical Engineering Journal, 2026)

Solar-driven green degradation of lignin toward sustainable aromatics via BiVO4/Zn4In2S7 S-scheme heterojunction - Qunshuai Li; Luxin Zhang; Weiwei Shi; Sishang Ge; Menglu Hu; Rong Chen (Chemical Engineering Journal, 2026)

Benzoic acid inhibits peach root growth and lateral root emergence by disrupting auxin homeostasis through salicylic acid accumulation - Qing Rong Zhang; Jilin Yao; Feiyang Ji; Zhilin Sun; Bing Bai; Jun Zhao; Huchen Li; Yueping Liu; Qingqin Cao; Qing Zhang; Ting Ting Xiao (Plant Cell Reports, 2026)

RETRACTED ARTICLE: Molecular mechanisms of flower color variation in Impatiens uliginosa: insights from transcriptome sequencing and functional analysis of the IuMYB1 gene in anthocyanin biosynthesis and pigmentation - Baiyang He; Yuteng Xue; Shanman Li; Xue Hu; Xiaoli Lou; Jiwei Wang; Huang Deng; Shunming Zhang; Chao Luo; Yuhong Rong (Physiology and Molecular Biology of Plants, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Ratiometric near-infrared fluorescent probe for imaging Peroxynitrite fluxes in rheumatoid arthritis and drug-induced liver injury models - Rong Li; Ruifang Wang; Minglu Li; Liyun Zhang (Analytica Chimica Acta, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

Phosphorus limitation and manganese toxicity induced by high nitrogen inputs suppress plant biomass - Jiapu Li; Xuebin Yan; Jordi Sardans; Josep Peñuelas; Shiting Hong; Peng Wang; Pinwei Zhang; Rong Song; Yanwen Zhao; Yong Li; Hui Guo (Plant and Soil, 2026)

Mechanisms and Applications of Gas Flow in Coal Seams Considering the Effects of Cross-Section Shape and Surface Roughness - Shouqing Lu; Yongfu Liu; Zhentao Li; Yujin Qin; Rong Zhang; Zhanyou Sa; Jie Liu; Yongliang Zhang (Rock Mechanics and Rock Engineering, 2026)

The Study on the Biological Characteristics of Photobacterium damselae subsp. damselae Affected by the Deletion of the Iron Uptake System Genes tonB1 and tonB2 - Hua Jiang; Yufei Ji; Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Xiaojun Rong; Aijun Ma; Shuyi Li; Zheng Zhang (Fishes, 2026)
Photobacterium damselae subsp. damselae (PDD), a marine fish pathogen, has an unclear contribution of tonB genes to iron acquisition and pathogenicity. ΔtonB1-PDD and ΔtonB2-PDD mutants as well as their complemented strains were generated via homologous recombination from the virulent strain PDD1605. Growth was evaluated by monitoring OD600 with viable-count calibration, intracellular iron was measured using a colorimetric assay, biofilm was detected by crystal violet staining, transcription was analyzed through qRT-PCR, and pathogenicity was assessed via an 8-day intramuscular challenge in black rockfish (Sebastes schlegelii). Under iron limitation induced by 100 μM 2,2′-dipyridyl, the maximum density decreased from 4.51 × 108 CFU/mL in wild-type (WT-PDD) to 4.00 × 108 and 3.64 × 108 CFU/mL in ΔtonB1-PDD and ΔtonB2-PDD respectively, and was largely restored after complementation. The intracellular iron content declined from 3.75 × 10−4 ± 4.00 × 10−6 nmol/106 cells in WT-PDD to 3.13 × 10−4 ± 1.05 × 10−5 nmol/106 cells in ΔtonB1-PDD and 2.55 × 10−4 ± 2.00 × 10−5 nmol/106 cells in ΔtonB2-PDD. Compared with WT-PDD, biofilm formation was reduced by 22.1% in ΔtonB1-PDD and by 24.8% in ΔtonB2-PDD. Deletion of tonB2 induced mild yet statistically significant transcriptional alterations in multiple iron acquisition and virulence-related genes, while colony morphology, swarming motility, hemolysis, phospholipase activity, biochemical traits, and antimicrobial susceptibility remained unchanged. In the high-dose challenge assay, WT-PDD caused 100% mortality within 2 days, whereas ΔtonB1-PDD and ΔtonB2-PDD caused 17/20 and 18/20 deaths respectively; all infected groups reached 100% mortality by day 3. In the low-dose challenge assay, WT-PDD, ΔtonB1-PDD, and ΔtonB2-PDD caused 12/20, 12/20, and 13/20 deaths by day 2, with cumulative mortalities reaching 80%, 70%, and 80% by day 8, respectively. Kaplan–Meier analysis detected no significant differences among the survival curves at either challenge dose. These findings suggest that tonB1 and tonB2 play roles in iron acquisition, low-iron adaptation, and biofilm formation, with tonB2 deletion exerting greater effects on growth and intracellular iron accumulation under iron-limited conditions.

Assessing impacts of vertical mixing parameterizations on ENSO simulation in a ROMS-based hybrid coupled model - Yinnan Li; Yang Yu; Maonan Chen; Chuan Gao; Hongna Wang; Liu Yang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Rapid Determination of Tight Rock Permeability Using Early-Time Transient Pulse-Decay Data - Minghao Yi; Chaoqi Yang; Liang Wang; Rong Zhang; Kaizhong Zhang; Shuqing Li (Rock Mechanics and Rock Engineering, 2026)

Retraction notice to “Algorithm developed for dynamic quantification of coal consumption for and emission from rural winter heating” [Sci. Total Environ. 737 (2020) 139762] - Yuzhe Zhang; Guorui Zhi; Sicong Guo; Wenjing Jin; Lei Wang; Jinhong Du; Miaomiao Cheng; Zhigang Xue; Yisheng Xu; Rong Shi; Yajing Lu; Hongyan Dang; et al. (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Cenozoic evolution of the Yangtze River, China: Constraints from quantitative detrital zircon UPb provenance modeling - Qiqi Song; Jie Hu; Zhiwu Li; Shengbiao Hu; Rong Tang; Chenghao Wei; Tianyao Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Impact of fulvic acid on copper exposure in Ulva prolifera: Integrative insights from growth, physiology, transcriptomics, and physico-chemical characteristics - Tongpeng Jia; Geqi Zhang; Yahe Li; Xinchuan Yang; Nianjun Xu; Rong Xiang (Journal of Hazardous Materials, 2026)

Species-specific bioaccumulation and biotransformation of antibiotics shape differential toxicological effects in a multi-level aquatic community - Bin Wang; Hailing Zhou; Mengting Li; Bingyu Shen; Lidan Zhang; Jiayi Yang; Yushi Fang; You Zi; Jinmei Chen; Yujie He; Rong Ji (Journal of Hazardous Materials, 2026)

Reducing environmental footprints of food consumption in urban and rural China: A scenario-based optimization towards sustainable diets - Zheng Guo; Junjie Zhao; Sophia Shuang Chen; Jialong Xu; Yi Zhang; Rong Li; Yingyi Ma; Enkang Li; Giri Raj Kattel (Journal of Environmental Management, 2026)

Separation of V/Cr from the leachate of vanadium slag by solvent extraction to prepare vanadium electrolyte - Rong Jiang; Limei Chen; Qiuxiang Liu; Mingyu Wang; Guiqing Zhang; Qinggang Li; Wenjuan Guan; Shengxi Wu; XinSheng Wu (Hydrometallurgy, 2026)

The dual role of H2 in a hydrogen-rich atmosphere: mechanisms of coke dissolution loss inhibition and strength enhancement - Jialong Yao; An Li; Rong Ge; Jingchong Yan; Zhanku Li; Weidong Zhang; Zhicai Wang; Zhiping Lei; Shibiao Ren; Hengfu Shui (Fuel, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

Chymotrypsin-based LC-MS for accurate quantification of 11 major food allergens in heat-processed foods overcoming Maillard reaction challenges - Siyi Li; Meizhen Zhou; Ruijie Chen; Yutong Xu; Yumeng Zhao; Yingnan Shencheng; Shuyan Liu; Rong Zhang; Min Gao; Yi Li; Shupeng Yang (Food Chemistry, 2026)

From byproduct to bioresource: Antioxidant potential, flavor profile, and microbiological quality of recovered water from freeze-dried and rotary evaporation dried Muscat grapes - Mengru Li; Yilei Huo; Pengkai Tang; Xiaoying Zhang; Haiyu Du; Wuernisha Kadeer; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Sandwich nanofiber membrane with high thermal conductivity boundary for high-flux membrane distillation - Lingling Zhong; Ruiyang Zhao; Zening Li; Rong Gao; Xinbo Zhang (Environmental Research, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

China could simultaneously increase wheat yield and nitrogen use efficiency under the temperature rise of 1 ℃ through optimal crop managements - Kaiyuan Gong; Shuoqiu Ding; Yadong Luo; Yinghua Zhang; Xiao Wang; Fengying Duan; Xia Li; Liangbing Rong; Zhihao He; Hao Feng; Qiang Yu; Wenbin Zhou; et al. (European Journal of Agronomy, 2026)

Photocatalytic induced self-cleaning black@ZnO/CuO super hydrophilic heterojunction modified carbon fiber composite membrane and resource recovery of degreasing wastewater - Wenwen Sun; Li Yin; De Sun; Mingwei Ma; Ao Rong; Guoliang Zhang (Desalination, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Phosphorus–boron synergistic carbonization/dormancy strategy enables polyurethane foams with aging enhanced fire safety - Shuang Li; Hai-Bo Zhao; Ming-Jun Chen; Lei He; Lin Zhang; Fu-Rong Zeng; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

GmHMGR6 enhances salt stress tolerance in soybean through modulation of nitrogen metabolism - Xinjie Feng; Hongzhen Liu; Yingyue Zhang; Yanping Li; Zhengxing Guo; Rong Bao; Xiuli Zhang; Xinying Liu; Huihui Zhang (Plant Cell Reports, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Differential Enrichment of Deep Shale Gas in Southeastern Sichuan Basin: Dynamic Evolution and Preservation Mechanisms - Ke Zhang; Haikuan Nie; Songhang Zhang; Tianwu Xu; Zhujiang Liu; Chuanxiang Sun; Chengxiang Wan; Wei Dang; Pei Li; Jia Rong; Shuheng Tang (Journal of Earth Science, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Kinetic Characteristics and Migration Behavior of Fractal-Based Sub-Diffusion of Coal Reservoir Gas under Anomalous Spatio-Temporal Conditions - Zhenyang Wang; Shuo Zhang; Congmeng Hao; Lu Bai; Rong Zhang; Guanhua Ni; Zhen Liu; Zhao Li; Jiaxuan Liu (Natural Resources Research, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

First case report: Severe mass mortality in intensively cultured black scraper (Thamnaconus modestus) caused by nervous necrosis virus infection - Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Zhen Meng; Yingeng Wang; Xiaojun Rong; Meijie Liao; Bin Li; Wenlong Li; Xinzhang Ji; Xiaoyan Cheng; Zheng Zhang (Aquaculture, 2026)

Adaptive fusion of acceleration and velocity records using machine learning for improved ground motion modeling - Mianshui Rong; Qingxu Zhao; Bin Zhang; Aixia Dou; Jixin Wang; Xiaoshan Kong; Xiaojun Li (Soil Dynamics and Earthquake Engineering, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

High-performance conductive ceramic membrane coupling with electrochemical membrane bioreactor (EMBR) for advanced wastewater treatment: Optimization of fabrication approach and application conditions - Lingyi Kong; Yisong Hu; Zhenqi Xu; Qiaoqing Zhang; Guanqian Wang; Xiaobao Li; Rong Chen (Journal of Water Process Engineering, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

6H2L, a novel derivative of bifendate, dually suppresses glycolysis and glutaminolysis in hepatocellular carcinoma via inhibiting YAP stability - Beibei Zhang; Kaixuan Sheng; Yue Yan; Xinlei Wang; Xinning Cheng; Rong Liao; Zhiyi Yang; Mengyi Li; Fan Wang; Qi Qi; Yu Wang; Chenglin Li (Chemico-Biological Interactions, 2026)

Contrasting effects of iron oxides versus bentonite on the biodegradation and conversion of dissolved organic matter derived from single and mixed plant litters - Wen Xiao; Xue Li; Shuangshuang Jiang; Minghui Rong; Xinhou Zhang (Plant and Soil, 2026)

Comparative metagenomics of three distinct biological soil crusts in sandy land of Northern China - Rong Hui; Yalin Zhou; Hongxia Zhang; Huijuan Tan; Xinrong Li (Plant and Soil, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Discovery of pyrrolo[2,3-d]pyrimidine derivatives with inhibitory effect on liver cancer stem cell - Xuecong Zhang; Xuechun Chen; Liwei Wang; Yiyuan Chang; Jiaxin Li; Jijian Yang; Dongxuan Ni; Ruihan Zhang; Rong Liu; Weilie Xiao (Medicinal Chemistry Research, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Debris flow vulnerability assessment in the Eastern Tibetan Plateau using integrated UAV-SLAM 3D reconstruction: Shuihaizigou Gully case study - Haoyu Li; Jianqiang Zhang; Yunyuan Li; Lili Zhang; Zaiyang Ming; Rong Chen (Landslides, 2026)

Phytolith-occluded carbon sequestration by Suaeda salsa in the Yellow River Delta estuarine channel shifts: opportunities for improved salt marsh management - Li Zhang; Bowen Rong; Changzi Ge; Xiangxing Gao; Cuilian Guo; Shaobin Han (Journal of Soils and Sediments, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Shrub litter promotes more mineral-associated organic carbon formation than graminoid litter via enhanced microbial transformation in Sanjiang plain wetlands, Northeastern China - Xue Li; Minghui Rong; Bixiu Wang; Chongwen Sun; Xinhou Zhang (Applied Soil Ecology, 2026)

Layered manure facilitates phosphorus mobilization mediated by putative keystone taxa among phoD-harboring bacteria - Linkang Chen; Rong Huang; Xiaoyan Tang; Bo Kang; Yijian Zheng; Zongjin Zhang; Changquan Wang; Bing Li (Applied Soil Ecology, 2026)

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Spatiotemporal Patterns, Driving Mechanisms and Responses of Soil Drought to Meteorological Drought in the Yellow River Basin of China - Fei Wang; Wenhan Yu; Yi Zhang; Hexin Lai; Mengting Du; Qian Xu; Rong Li; Ruyi Men; Haoyu Li; Kai Feng; Shikai Gao; Yanbin Li; et al. (International Journal of Climatology, 2026)
With the escalation of global warming, the potential for land evaporation in the Yellow River Basin (YRB) has increased remarkably, and the problem of soil drought has become increasingly prominent. This not only restricts the development of the agricultural economy in the basin, but also intensifies the disparity between water availability and demand, and exerts a profound influence on the ecological security of the basin. In light of this, this study focuses on soil moisture in the YRB from 2000 to 2022, and conducts an in‐depth analysis of the temporal evolution, spatial patterns, abrupt change characteristics as well as the driving forces of soil drought by calculating the Standardised Soil Moisture Index (SSMI). The results show that: (1) Soil drought in the YRB from 2000 to 2022 exhibited a decreasing trend. A negative abrupt change point occurred in February 2004, indicating a sudden intensification of arid conditions. The soil drought in the Above Longyangxia (AL) region exhibited the most significant decreasing trend in September. (2) The most severe soil drought occurred in 2006, and the drought was most intense in November of that year, when the drought‐affected area reaching 86.96%. The severely drought‐stricken areas were predominantly concentrated in the central and northern regions of the basin. (3) The SSMI in the second‐level sub‐regions of the YRB exhibits three types of abrupt changes: increase to decrease, intermittent increase, and decrease to increase, and shows a clear trend from upstream to downstream. (4) The results of cross‐wavelet analysis indicate that soil moisture‐absolute humidity‐soil temperature is the best explanatory combination for soil drought. (5) The slopes of the small‐ and medium‐scale fittings in the AL region are 0.5021 and 0.2584, respectively, and the corresponding mean values of meteorological drought severity are 0.87 and 2.57, respectively. Drought events in the YRB are mainly of medium/short duration and low severity, and soil drought severity tends to increase with the intensification of meteorological drought. This study reveals the spatiotemporal variation patterns of soil drought in the YRB, as well as the responses of climate to soil drought. These findings provide a scientific basis for drought resistance and ecological protection within the basin.

Research progress on the fermentation characterization of non- Saccharomyces yeasts in fruit wines: a review - Rong Zhang; Xiaoyan Hou; Qigao Fan; Kaidi Hu; Lunqiong Hou; Ning Kang; Ziyuan Ou; Ning Zhao; Qin Li; Aiping Liu; Yong Yang; Guoquan Han; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Isolation, identification, and disease-protective potential of Pseudomonas monsensis DBFF02 against Saprolegnia infection in grass carp - Guofan Zhang; Kunyan Li; Yuyuan Peng; Simei He; Chen Li; Rong Fan; Jiajie Xie; Linger Qian; Xinran Long; Jiayi Wang; Jiatao Yang; Yanmin He; et al. (Aquaculture, 2026)

Unraveling the flame retardant mechanism of protein-rich matrix recovered from anaerobic sludge: The governing role of microstructural characteristics - Bo Zhang; Gaojun Wang; Yinghong Dong; Qian Li; Yu-You Li; Rong Chen (Water Research, 2026)

Bioaerosol multi-pollutant source localization in urban microclimates using an improved particle swarm optimization method with restricted search capabilities - Zhijian Liu; Yixiang Ma; Chenxing Hu; Haiyang Liu; Hongliang Zhang; Xin Li; Zhenhai Sun; Rui Rong; Zhijian Dong; Xiang Zhao; Guangpeng Yao (Sustainable Cities and Society, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Antifungal activity and action mechanisms of 2, 4-Di-tert-butylphenol from Bacillus amyloliquefaciens Z-7 volatile organic compounds against Verticillium dahliae - Hong Tan; Jie Zeng; Jinyi Wu; Chunsheng Wang; Lihua Zhang; Anlong Hu; Zhibo Zhao; Youhua Long; Rong Fan; Xiaoping Hu; Rongyu Li (Pesticide Biochemistry and Physiology, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

From green revolution to multigene revolution: Breeding high-yield rice by design - Bo Zhang; Qingli Wen; Wenrui Feng; Rong Wang; Wenbo Liu; Wen Huang; Ahmed Khatab; Jiayang Li; Yongzhong Xing (Molecular Plant, 2026)

Species synergy effects on milky aroma are conditioned by moisture-gradient driven pore evolution of protein–fat networks in fermented sausages - Futong Song; Ruren Li; Di Zhang; Jiaqi Zhao; Yafang Yao; Nan Zhang; Liangyan Rong (Meat Science, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Remediation effects of humic acid and hydroxyapatite on cadmium-contaminated alkaline wheat soil and its microbial community response: A field trial - Yineng Lu; Haoyu Yue; Rong Tan; Zihao Ding; Geng Chen; Shuangting Zhang; Ziyi Li; Ram Proshad; Xiuwen Cheng; Zhuanjun Zhao (Journal of Environmental Sciences, 2026)

Citral-loaded PVA-PVP hydrogel pad: Preparation, physicochemical properties, characterization, and application for blueberry preservation - Haifeng Rong; Wenna Li; Yuxuan Li; Sixu Lin; Runan Zhao; Yufeng Xu; Bingxin Sun; Yunhe Zhang; Xuerui Yan (Food Packaging and Shelf Life, 2026)

High-efficiency solar-driven photothermal membrane distillation via permeate-side interfacial heating - Qian Yu; Mengfei Xie; Rong Chen; Kuiling Li; Liqiu Zhang; Bo Pan; XueJun Pan; Junhui Zhang; Dan Qu (Desalination, 2026)

Dual-configuration arabinogalactan-II synergizes with rhamnogalacturonan-I in Lycium barbarum pectin to construct an intestinal anti-inflammatory glycan scaffold - Guoqiang Li; Yajun Qiao; Qiannan Wang; Xingfang Zhang; Lin Rong; Lixin Wei; Tingting Gao; Hongtao Bi (Carbohydrate Polymers, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Impacts of balconies on air quality within idealized building array: CFD modelling with solar radiation - Guoxing Chen; Guoqiang Zhang; Yanni Liu; Riyi Li; Li Rong (Building and Environment, 2026)

Unveiling animal death cognition: the role of social systems - Junjie Mu; Xi Yang; Yongbo Li; Yu Huan; Boyi Zhang; James R. Anderson; Rong Hou; Baoguo Li (Science China Life Sciences, 2026)

Imbalanced Si:N Alters Lipid Production and Photosynthesis in the Marine Diatom Phaeodactylum tricornutum and Dinoflagellate Prorocentrum donghaiense - Jiaxuan Cui; Chuanli Zhang; Rong Bi; Yunyun Zhuang; Xiaoqian Pan; Xiao Qin; Zhong Cao; Hailong Zhang; Li Li; Yang Ding; Meixun Zhao (Journal of Ocean University of China, 2026)

Nutrient input strategies mediate the link of rhizosphere soil microbiomes with rice productivity: Based on a decade-long field experiment - Ning Su; Xiangmin Rong; Qiaorong Li; Yansong Xiao; Guixian Xie; Chang Tian; Yali Kong; Yuping Zhang; Gongwen Luo (Agriculture, Ecosystems & Environment, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

A joint optimization method for weight estimation and re-identification based on a cattle back semantic disentanglement model - Yuqi Zhang; Longxiang Li; Hui Kang; Shiyuan Liang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

Deciphering the 2-MIB production mechanism in Actinobacteria: the interplay of synthesis enzymes, nutrient metabolism, and seasonal regime - Honghong Guo; Rong Li; Xuanzi Zhangsun; Han Gao; Ruopu Yuan; Shuai Zhao; Jianwei Bu; Haihan Zhang; Tinglin Huang (Water Research, 2026)

Successful establishment of denitrification-enhanced anaerobic digestion with nitrate as an exogenous stimulant for effective hydrolysis and methanogenesis of N, N-dimethylformamide-containing wastewater - Zhe Kong; Tao Zhang; Yao Xu; Yong Hu; Chao Rong; Yu-You Li (Water Research, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Methionine-driven covalent chelation of Zn2+ by linusorb: a paradigm in hydrophobic cyclic peptide metal binding - Yi-kang Zhang; Du-jian Deng; Zhong-yi Luo; Wan-nan Wang; Jun-le Li; Shao-rong Zhang; Jia-li Li; Jia-zi Chen; Yong Wang; Zi-zhe Cai (Food Chemistry, 2026)

Moisture and interspecies interactions shape microbial communities and metabolites to define the sensory profile of fermented sausages - Di Zhang; Ruren Li; Liangyan Rong; Ying Xu; Futong Song; Nan Zhang; Ting Sun; Guoliang Li (Food Chemistry, 2026)

Lipid oxidation-mediated protein–starch interactions in walnut cookies: Influence of oil composition on microstructure, texture, and starch retrogradation - Li Fang; Yujin Zhang; Rong Chen; Yuanfa Liu; Xiuhang Chai (Food Chemistry, 2026)

When city lights turn blue: Spectral ALAN exposure, LED lighting, and diabetes prevalence using SDGSAT-1 - Yanqing Xu; Ruoyu Dong; Tingting Li; Sujin Zhang; Yan Liu; Yuchen Li; Kenan Li; Xiaobo Feng; Shuang Rong (Environmental Pollution, 2026)

The climatic response of inter- and intra-annual tree ring stable carbon isotopes of larch trees in the Qinling Mountains, central China - Mingyang Sun; Chao Li; Rong Fan; Yuting Fan; Feiyu Chen; Yuanjie Wang; Huan Zhang; Ninglian Wang (Dendrochronologia, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

From the perspective of resource recovery: Electrochemical treatment technology system for heavy metal complex wastewater - Rong Wang; Chenyang Zhang; Junyi Li; Wei Sun (Chemical Engineering Journal, 2026)

Aluminum modulation of cobalt states in perovskite for higher alcohols synthesis from syngas - Pengfei Song; Rong Liu; Zihan Shen; Yuwei Zhang; Xijun Li; Chenxi Zhang; Fei Wei; Yuan Liu; Chuan Wang; Zhichuan J. Xu (Chemical Engineering Journal, 2026)

Investigating the synergistic role of dual solid additives in morphology engineering and photogenerated charge dynamics for high-efficiency all-polymer solar cells - Liping Zhou; Tengxiang Gao; Shuonan Li; Wei Zhang; Rong Hu (Chemical Engineering Journal, 2026)

Magnetic biochar combined with digestate bioaugmentation synergistically accelerates the recovery of a collapsed anaerobic digestion system - Bao-Shan Xing; Yong-Ning Feng; Jia-Yi Liu; Yi Zhang; Guangyin Zhen; Samir Ibrahim Gadow; Rong Chen; Xiaochang C. Wang; Yu-You Li (Chemical Engineering Journal, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Photoelectron-driven modulation of carbon metabolism enhances hydrogen production in a ZnIn2S4-Shewanella oneidensis biohybrid system - Xue-Meng Wang; Hao-Yu Li; Kai-Li Wang; Zhi-Xuan Zhang; Yu-Xin Cao; Ya-Lian Ma; Rong Chen (Bioresource Technology, 2026)

Bioaerosol emission in public washroom under different time intervals of working day and critical exposure time for sanitary workers - Wajid Ali; Zi-qi Yang; Chun-shu Tian; Rui-wen Li; Xu Zhang; Qing Yan; Ke-yu Chen; Si-bo Cheng; Rong-xin Wang; Cheng Yan (Building and Environment, 2026)

Higher aridity in alpine grasslands discourages soil organic carbon accumulation by microorganisms - Jia Li; Xia Wang; Ya Rong Zhang; Ya Zhen Li; Meng Han Yuan; Yun Fei Zhao; Wen Hui Duan; Jie Yi Xia; Zi Yang Niu (Plant and Soil, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Attenuation Characteristics of Blast-Induced Stress Waves from Field Measurements - Kai Rong; Zong-Xian Zhang; José A. Sanchidrián; Adeyemi Aladejare; Li-Yuan Chi; Pablo Segarra (Geotechnical and Geological Engineering, 2026)
The attenuation characteristics of stress waves were studied based on 16 small-scale single-row blast tests at Otanmäki mine. In each test, the primary joint orientation was documented, two monitoring points were positioned at different distances from the blastholes, and the particle velocities in three orthogonal directions were measured. Seismic curves for the three components are shown under both short- and long-delay blasts. The attenuation laws of peak particle velocity ( PPV ) vector resultant derived from the radial, transverse and vertical particle velocity time histories, as well as seismic energy, with respect to scaled distance under three different primary joint orientations were analysed. The results show that the attenuation of stress waves is smallest when joints dipping into the face and greatest when joints dipping out of the face, and this difference may be attributed to the variations in the energy transmission efficiency of stress waves across joints under different incident angles. The geometric attenuation law of stress waves was analysed, which varies with the relationship between measuring distance and wavelength. According to this law, a modified charge scaling law was proposed in the form of a piecewise function. The validation results indicate that this law has practical applicability to a certain extent.

Multidisciplinary modeling and dynamic Kriging assisted optimization for suborbital reusable launch vehicle - Teng Long; Haoda Li; Renhe Shi; Rong Chen; Baoshou Zhang; Nianhui Ye (Advances in Space Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

USP7-stabilized CEBPB promotes HpSCC progression by upregulating IL6 to activate the JAK2/STAT3 signaling - Honghui Li; Rong Fan; Yiping Qu; Yuan Shao; Yanxia Bai; Chongwen Xu; Jinsong Hu; Xiaozhi Zhang (Molecular and Cellular Biochemistry, 2026)

Seco-iridoid and lignans from Gymnosporia acuminata - Yang Liu; Wenhui Suo; Qinggui Li; Qingqing Luo; Rong Wang; Xiaoke Zhang; Changwei Song; Lingjie Meng (Natural Product Research, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Behavioral, Metabolic, and Monoaminergic Responses to Cooked Diets in Southern Catfish (Silurus meridionalis) - Qiushi Yang; Zhimin Zhang; Tingting Xu; Wenhan Li; Huacheng Li; Rong Tang; Yale Deng; Liqin Yu; Xi Zhang; Li Li; Dapeng Li (Fishes, 2026)
Diet form is increasingly recognized as a welfare-relevant factor in intensive aquaculture, yet the effects of feed cooking on fish behavioral and physiological welfare remain poorly characterized. Juvenile southern catfish (Silurus meridionalis; 6.18 ± 0.52 g) were reared for 6 weeks in an indoor recirculating aquaculture system and fed either raw grass carp (Ctenopharyngodon idella) muscle (fish fed raw muscle, FR) or cooked grass carp muscle (fish fed cooked muscle, FC; 15 min ramp to ~100 °C followed by 2–3 min at ~100 °C). Locomotor activity and anxiety-like behavior were assessed using the open-field test and an annular light–dark preference assay, respectively. Flow-through respirometry further revealed a significantly lower standard metabolic rate (SMR) in FC fish than in FR fish, decreasing from 10.30 to 6.83, which represents a 33.7% reduction. Endocrine and biochemical analyses showed that cooking significantly decreased serum total triiodothyronine (T3) by 23.8%, whereas routine serum biochemical indices remained unchanged. In brain tissue, dopamine (DA) was significantly reduced by 7.2% in the FC group, and RT-qPCR analysis of dopamine-related genes further showed a significant downregulation of the rate-limiting synthesis gene th. These results indicate that cooking primarily downshifts the activity-energy axis in southern catfish and is accompanied by coordinated thyroid and dopaminergic changes. To our knowledge, this is the first integrated study to evaluate the behavioral, metabolic, and neuroendocrine effects of cooked feed in S. meridionalis, providing a short-term phenotypic baseline for assessing welfare-relevant feeding scenarios in aquaculture.

Bayesian inversion method for soil layer velocity structures based on the earthquake horizontal-to-vertical spectral ratio and its applications - Mianshui Rong; Yuxiao Zhang; Xiaojun Li; Pinghe Ni; Jixin Wang (Soil Dynamics and Earthquake Engineering, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Antifungal mechanisms of Bacillus velezensis Shannan.BV80-12 extracellular metabolites against the citrus postharvest pathogen Penicillium italicum - Rong Wang; Yali Tan; Feiyan Dong; Jiao Yang; Xiao Li; Tong Gu; Jialan Zhang; Li Li; Mengxiang Gao (Postharvest Biology and Technology, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

Mitigating 2-MIB and odor-producing cyanobacteria in a shallow drinking-water reservoir using sponge‑iron-assisted water-lifting aeration - Fei Zhang; Rong Li; Hao mu; Yuhai Zhuo; Zhi Yang; Tinglin Huang; Nan Li (Journal of Water Process Engineering, 2026)

Association between plasma trace metals and non-alcoholic fatty liver disease among rural women in Southern China - Qiumei Liu; Xiaolin Li; Yufu Lu; Kaisheng Teng; Xiaoting Mo; Linhai Zhao; Songju Wu; Jiahui Rong; Qinyi Guan; Lei Luo; Tiantian Zhang; Yujian Liang; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Boron fortifies a dual barrier in rice roots: How Casparian strip reinforcement and cell wall remodeling restrict cadmium entry - Zhihong Guo; Min Nie; Ting Li; Changfeng Ding; Gaoxiang Huang; Zhengfu Yue; Yurong Wang; Taolin Zhang; Rong Huang; Xingxiang Wang (Journal of Hazardous Materials, 2026)

Aerobic biodegradation of acesulfame by sediment-enriched microbial consortia: Kinetics, pathway, and microbial mechanism - Xiaoxue Zhang; Jianwei Chen; Yuxuan Li; Rong Tang; Tianyue Zhu; Yong Yuan (Journal of Environmental Management, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Soil hydrology affected by crushed rock content modulates the alpine ecological restoration: implications from soil reconstruction - Ruixuan Li; Jianfei Wang; Chengjing He; Rong Sun; Qing Zhang; Qinghua Liu; Xueyong Pang (Journal of Environmental Management, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

High hydrostatic pressure mitigates light-induced degradation of volatiles and phenolic compounds in seabuckthorn pear blends - Jianfeng Wang; Yonghao Chen; Rong Zhang; Shengbin Ma; Faisal Eudes Sam; Jixin Li; Yang Bi; Yumei Jiang (Food Chemistry, 2026)

Tropomyosin-targeted LC-MS/MS for quantitative detection of molluscan allergens in foods: Method validation and application - Yumeng Zhao; Peijie Yang; Yingnan Shencheng; Siyi Li; Meizhen Zhou; Min Gao; Feng Ye; Rong Zhang; Ya Zhang; Yi Li; Shupeng Yang (Food Chemistry, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Antibacterial mechanism of Sanguinarine against Klebsiella pneumoniae and its efficacy in reducing bacterial contamination in milk - Ruiying Wang; Diangang Han; Tianlong Hu; Rong Zhao; Yanlin Li; Qiqi Pu; Ju Zeng; Xiong Dai; Long Zhang; Jige Xin (Food Bioscience, 2026)

Functional division of labor within defined yeast consortia drives flavor formation during early solid-state fermentation of sichuan shai vinegar - Jiajie Zhu; Yuting Liao; Yulin Zhao; Jun Liu; Zhicheng Li; Xiangpeng Kong; Suyi Zhang; Chuan Song; Qixu Fu; Xianbin Wang; Ruiqi Xue; Xuemei Shi; et al. (Food Microbiology, 2026)

Achieving sustainable rice production with reduced nitrogen fertilization through unlocking soil organic nitrogen mineralization by alleviating microbial carbon limitation - Ning Su; Xiangmin Rong; Yao Liu; Junru Li; Runjia Yin; Guixian Xie; Yuping Zhang; Gongwen Luo (Field Crops Research, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Efficient floor response spectrum estimation via a condensation-based modal combination framework - Fengze Li; Xudong Zhi; Duozhi Wang; Nawawi Chouw; Rong Zhang; Feng Fan (Engineering Structures, 2026)

Design of green multifunctional mesoporous nanosheets for trace biomarker detection, AI-enhanced pollutant discrimination, and synergistic catalytic degradation - Zamar Daka; Yuqi Zhang; Jieli Li; Liying Yao; Chenxi Luo; Meng Tian; Xi Xia; Guowen Qin; Rong Jiang; Min Song; Shunli Ji (Chemical Engineering Journal, 2026)

Urbanisation magnifies the effect of innovative behaviour on avian persistence and extinction risk - Lingxue Li; Jiaxuan Jiang; Xinyu Guo; Xinyu Zhang; Yanfang Li; Ke Rong (Biological Conservation, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Efficacy and Safety of Temozolomide for the Treatment of Advanced or Recurrent Ependymoma: A Meta-Analysis - Rong Zhang; Binyan Liu; Zhuang Kang; Shenglan Li; Yingfan Sun; Jiachen Wang; Xin Yang; Shuo Yin; Feng Chen; Wenbin Li (Journal of Pharmaceutical Innovation, 2026)

Increasing phosphorus availability and dynamics enhance soil organic carbon and its sub-pools sequestration as consequence of phosphorus inputs - Yao Liu; Junru Li; Ning Su; Xiangmin Rong; Yuping Zhang; Xianjun Zeng; Jianwei Peng; Gongwen Luo (Soil Ecology Letters, 2026)

The influence of rewetting intensity on soil priming after drought - Yijin Lv; Rui Zhang; Rong Li; Zhenqing Shi (Applied Soil Ecology, 2026)

A CBAM-integrated deep convolutional neural network for weather radar echo correction to overcome terrain occlusion challenge - Hao Wang; Zhihao Liu; Fugui Zhang; Zhi Li; Qiangyu Zeng; Tiantian Yu; Rong Yang (Advances in Space Research, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Tidal Modulation of Waves over the Changjiang River Estuary: Long-Term Observations and Coupled Modeling - Zhikun Zhang; Zengrui Rong; Xin Meng; Pixue Li; Tao Qin (Journal of Marine Science and Engineering, 2026)
Tidal-scale wave modulation is a critical yet complex process in macro-tidal estuaries. This study investigates semidiurnal wave modulations in the Changjiang River Estuary (CRE) using unique, long-term in situ observations and high-resolution ADCIRC–SWAN coupled simulations. Pronounced semidiurnal signals are identified in significant wave height (Hs), mean wave period, and wave direction. Observational results demonstrate that the modulation intensity is highest in Hangzhou Bay and the CRE mouth, decreasing gradually offshore. A key finding is that semidiurnal Hs maxima systematically coincide with peak flood currents and precede high water by approximately three hours. Long-term records confirm that this modulation persists year-round and intensifies during energetic events such as typhoons. The expression of the tidal signal depends on wave composition: wind-sea-dominated conditions exhibit stronger period modulation, whereas swell-dominated conditions favor coherent Hs modulation as kinematic tidal effects remain more apparent in the absence of strong local wind forcing. Numerical sensitivity experiments demonstrate that tidal currents are the primary driver of the observed wave modulation, while water-level effects are largely confined to shallow shoals. The results highlight that accurately reproducing the observed frequency–directional structure requires the inclusion of current-induced Doppler shifts and refraction. Beyond the classical following-current effects, the analysis suggests that the spatial deceleration of currents along the wave path acts as a kinematic trap that focuses wave action and sustains Hs intensification. This mechanism provides a physically plausible explanation for the observed phase relationship and points to the non-local nature of estuarine wave dynamics, where the wave state appears as an integrated response to cumulative current gradients along the propagation path. These findings emphasize the necessity of incorporating wave–current coupling in future coastal modeling and hazard forecasting.

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

Food sources of the Synaptid Protankyra bidentata and its trophic competition with the sea cucumber Apostichopus japonicus in culture ponds - Jianlong Ge; Teng Lu; Jinjin Wang; Meijie Liao; Xiaojun Rong; Bin Li; Yingeng Wang; Yongxiang Yu; Chunyuan Wang; Zheng Zhang; Zhiqi Zhang (Aquaculture, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Salmonella virulence factor sptP activates the NLRP3/Caspase-1 pathway to induce pyroptosis and exacerbate intestinal injury in chicks - Bo Zhang; Ke Li; Hongya Yan; Rong Zhao; Zhenju Yuan; Changrui Xiao; Chengji Yang; Aiguo Xin (Veterinary Microbiology, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

Priorities for enhancing resilience of SDG causal network from a human-nature perspective - Yiming Su; Guangjin Zhou; Mingyuan Wang; Xiaoyun Li; Tao Liang; Lingqing Wang; Jian Hu; Jixi Gao; Wenwu Zhao; Siyuan Tao; Peter E. Holm; Jörg Rinklebe; et al. (Resources, Conservation and Recycling, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

Multi-omics reveals that Sophora alopecuroides lysine decarboxylase (SaLDC)-mediated polyamine metabolism enhances salt tolerance and early flowering in Arabidopsis - Yongli Tian; Rui Wang; Jing Su; Wenjuan Li; Ping Liu; Chengke Luo; Jiaojiao Qian; Danting Zhang; Peifu Li; Bin Wang; Rong Yang; Tianli Ma; et al. (Plant Science, 2026)

A low pH level in ripening pear tissue promotes the growth and pathogenicity of Alternaria alternata by causing ammonia accumulation and alkalization - Meiqi Gao; Rong Li; Yanxia Zhang; Puwei Yan; Xiwang Wang; Yue Xie; Miao Zhang; Yongcai Li (Physiological and Molecular Plant Pathology, 2026)

Synergistic transformation of alkylbisphenols (BPA, BPE, and BPF) mediated by ammonia-oxidizing bacteria and heterotrophic bacteria in nitrifying activated sludge - Hang Xu; Wenhui Zhang; Sicheng Zhu; Bingyu Shen; Xinyu Li; Bingqi Jiang; Lianhong Wang; Philippe F.X. Corvini; Max M. Häggblom; Rong Ji (Journal of Hazardous Materials, 2026)

Fungal–bacterial interactions at species and strain-level influence γ-aminobutyric acid and ethyl esters accumulation in a simulated fermentation system - Nan Zhang; Ruren Li; Lan Zhang; Di Zhang; Futong Song; Yafang Yao; Wenqian Li; Liangyan Rong (International Journal of Food Microbiology, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Inactivation of microbial and pest contamination in post-harvest wheat by plasma-activated gas - Sihong Ma; Pengyu Zhao; Tianyi Song; Zhengyu Wang; Shenghang Xu; Li Guo; Zifeng Wang; Jishen Zhang; Hao Zhang; Dingxin Liu; Xiaohua Wang; Mingzhe Rong (Food Control, 2026)

Alterations in cardiovascular biomarkers and gut microbiome associated with night shift work: Insights from the Chinese platform workers study - Tenglong Yan; Li Rong; Siyuan Wang; Xin Song; Binshuo Hu; Zhihui Wang; Xiaoshun Wang; Xiaowen Ding; Rui Guan; Hong Yu; Dongsheng Niu; Ying Zhang (Environmental Research, 2026)

High-performance fiber-based aerogel evaporator for solar desalination and wastewater purification - Yan Liang; Siqi Wu; Yujie Zhao; Ning Liu; Rong Tian; Jianbin Zhang; Yanhua Liu; Dianming Li; Libang Feng (Desalination, 2026)

Lattice distortion-driven electronic engineering of high-entropy alloys for efficient polysulfide catalysis in LiS batteries - Li Zhang; Yan Wang; Bo-Wen Lin; Rong-Rong Liang; Tian-Hui Dang; Zhuo Zhao (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Enhancing the photocatalytic membranes performance via lignin sacrificial modification - Qian Wang; Na Zhou; Yuhan Zhang; Hangtian Lu; Xinglin Li; Rong Xu; Zhengzhong Zhou (Chemical Engineering Journal, 2026)

Waste eggshell derived porous skeleton with dual functional CNT synergistically enhance the thermal property of PCMs for thermal management - Pei Li; Yuwei Fan; Xuyan Song; Yiyi Wang; Weijian Liu; Jia Liu; Han Sun; Xin-Rong Zhang (Bioresource Technology, 2026)

Reduced graphene oxide enhances emerging contaminants removal in anaerobic wastewater treatment: Synergistic role of adsorption and microbial metabolism - Lianxu Wang; Zixin Zhang; Youfei Zhou; Zhen Lei; Yuan Yang; Yu-You Li; Rong Chen (Bioresource Technology, 2026)

Study of the machine learning emission inversion method of the CUACE model on the basis of fused Fengyun observations - Tao Niu; Congwu Huang; Yiliang Jiang; Qi Jiang; Bihui Zhang; Hongli Liu; Rong Li; Yuzhan Xie; Tijian Wang (Atmospheric Pollution Research, 2026)

Comprehensive genomic analysis of the maize ACP gene family reveals ZmACP1-mediated salt stress tolerance in Arabidopsis - Yunhao Wu; Junyu Chen; Hanqiu Ge; Xing Rong; Yuchen Wang; Meiwang Zhang; Zhigang Li; Yingrui Xi; Junfeng Tang; Junyi Li; Ping Li; Baohua Wang; et al. (Plant Cell Reports, 2026)

FabH (β-Ketoacyl-ACP Synthase III) -- Promising Novel Antibacterial Target and Its Inhibitors - Gui-Wen Li; Qing-Yun Rong; Wen Zhang; Guo-Wu Rao; Quan Zheng (Medicinal Chemistry Research, 2026)

Tropical instability waves and their relationships with large-scale oceanic thermal conditions, revealed in ROMS-based hybrid coupled model of the tropical Pacific - Yinnan Li; Yang Yu; Chuan Gao; Hongna Wang; Rong-Hua Zhang (Journal of Oceanology and Limnology, 2026)

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Failure Behavior and Energy Evolution of Granite Containing Pre-existing Fissures Characterized by AE and DIC - Run-ze Zhang; Chuan-xin Rong; Bin Wang; Hua-qiao Xu; Yan-zhe Li; Yang Wang (Applied Geophysics, 2026)

ChronicDPipredictor: an interpretable deep learning framework for chemical chronic and subchronic toxicity assessment - Xuelin Sun; Jiaqi Chu; Rong Ni; Fengxi Liu; Yatong Zhang; Xiao Li (Molecular Diversity, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The MADS-box transcription factor AaRLMA serves a crucial function in sustaining the integrity of cell wall, orchestrating secondary metabolites biosynthesis, and modulating pathogenicity in Alternaria alternata - Rong Li; Yiyang Liu; Xiwang Wang; Pengfei Sun; Meiqi Gao; Yanxia Zhang; Yang Bi; Yongcai Li (Postharvest Biology and Technology, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

Sustained polyhydroxyalkanoate recovery from fermentative food wastewater in a one-stage mixed microbial culture system under aerobic dynamic discharge strategy: Effects of organic loading rate and substrate composition - Xiang Zhang; Ji Zhang; Gaojun Wang; Kexin Wang; Yanfang Ma; Qian Li; Yu-You Li; Rong Chen (Journal of Cleaner Production, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

Ti(IV)-incorporated covalent organic frameworks for efficient dark-photocatalytic reduction of U(VI) - Li-Ling Chen; Cheng-Peng Niu; Rui Zhang; Yun-Peng Wu; Zhen-Wen Zhang; Bin Lin; Cheng-Rong Zhang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Environmental Chemical Engineering, 2026)

Spatiotemporal dynamics of land-use carbon emission efficiency in the Yangtze River Delta Urban Agglomeration: Insights from a directed weighted network - Rong Li; Jiashu Zhang; Xiuyu Qu; Xintao Liu (Journal of Environmental Management, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Bionic cellulose fiber-based columnar solar evaporator with interfacial regulation for superfast water purification - Ying Qian; Zhexuan Lan; Shunfang Wen; Rong Liu; Haifeng Zhang; Ruiqing Li; Du Nie; Seeram Ramakrishna; Wei Zhang; Jiamu Dai (Desalination, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Self-assembly of bayberry-like porous BiVO4 nanospheres for self-powered marine underwater optical communication - Ping Wang; Shuai Ren; Kun Fu; Yizhou Lv; Yayue Wang; Ping Rong; Weipeng Chen; Jianhua Zhang; Xifei Li; Qi Yu (Chemical Engineering Journal, 2026)

Microwave-assisted pyrolysis of dyeing sludge: Reaction kinetics, elemental transformation, and heavy metal migration - Dekai Fan; Rong Xiao; Wahab Nasarul; Chunbao Zhou; Yingwen Zhang; Bang Yao; Li Chao; Jianjun Dai; Gul Urooj; Yingrui Ning; Peng Zhu; Chen Chen; et al. (Chemical Engineering Journal, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Decomplexation for resource recovery from heavy metal complex wastewater: mechanisms, challenges, and future roadmaps - Rong Wang; Chenyang Zhang; Shujuan Zhang; Wei Sun; Wenzhang Li (Chemical Engineering Journal, 2026)

Innovative utilization of waste printed circuit boards and coal gangue/ash for multifunctional glass-ceramics: structure-property insights via data-driven analysis - Yingwen Zhang; Lei Gao; Li Chao; Bang Yao; Dekai Fan; Chen Chen; Rong Xiao; Yingrui Ning; Peng Zhu; Urooj gul sandilo; Abeanezer Lukas Bassa; Nasarul Wahab; et al. (Chemical Engineering Journal, 2026)

Anode interface layers constructed in situ by multifunctional carbon dots for ultra-stable aqueous zinc-ion batteries - Qian-Li Ma; Xi-Rong Zhang; Bao-Juan Wang; Hao-Wen Sun; Huan-Ming Xiong (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Experiments, DFT and Toxicity Evaluation of the Degradation of Tris (2-Chloroethyl) Phosphate (TCEP) by Ultrasonically-activated Persulfate System - Zihui Xu; Zhiyong Gan; Gang Kang; Lucheng Zhang; Mingqing Zhang; Shilong Wu; Rong Li (Water, Air, & Soil Pollution, 2026)

Adsorption of Oxytetracycline Hydrochloride by Oxidatively Modified Biochar Particles: Performance and Mechanism - Rong Chen; Jianlin Zhou; Lingling Wang; Weiyin Liu; Zeyu Dai; Zhang Chen; Guoliang Chen; Zhixian Li (Water, Air, & Soil Pollution, 2026)

Unveiling the genetic architecture of stripe rust resistance in wheat: a region-specific GWAS in Xinjiang, China - Feifei Zhang; Rong Wang; Wenjuan Jiao; Wanlong He; Yuzhe Zhang; Na Sun; Bin Bai; Kemei Li; Yukun Cheng; Hongwei Geng (Theoretical and Applied Genetics, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Research progress on the chemical composition changes of traditional Chinese medicine before and after processing based on modern analytical techniques - Xuelin Zong; Yun Shi; Ying Zhao; Yuman Li; Rong Guo; Gengyi Shang; Chenfeng Zhang; Jinyang Shen; Xun Gao; Weidong Li; Kunming Qin (Phytochemistry Reviews, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Biota occurrence, accumulation, disposition and toxic effect of chlorinated paraffins - Huiming Zhang; Yutong Yang; Mu Zhang; Xue Li; Yan Zhang; Shufen Han; Rong Chen; Jun Yang; Jianyun Zhang (Environmental Geochemistry and Health, 2026)

Effects of Straw Returning on Physicochemical Properties and Microbial Characteristics of Agricultural Soil - Tantan Zhang; Shiqiang Ge; Rong Gan; Siyuan He; Fuyuan Duan; Lin Li (Current Microbiology, 2026)

Integrating an CNOP analysis into a deep learning model to identify optimal initial errors for 2020–2022 La Niña prediction - Lingjiang Tao; Rong-Hua Zhang; Wansuo Duan; Lu Zhou; Tiaoye Li (Climate Dynamics, 2026)

Organic fertilization improves activities of phosphomonoesters hydrolase in rhizosphere to facilitate phosphorus acquisition in cucumber and accumulates organic phosphorus in soil - Bingshuang Wang; Yuan Wang; Xihe Zhang; Xiaodan Hu; Shujun Li; Yifei Sun; Yang Wang; Yan Sun; Ziwei Dai; Yunsheng Lou; Rong Li; Guohua Xu; et al. (Applied Soil Ecology, 2026)

Herder cooperatives vs. independent herders in Inner Mongolia: A comparative analysis of multi-dimensional efficiency - Jiuzhou Jin; Ruiyao Zhang; Pengpeng Dou; Rong Zhi; Ping Li (Agricultural Systems, 2026)

Status and risk assessment of antibiotic contamination of surface waters in China: a systematic review and meta-analysis - Rong Li; Lucheng Zhang; Lin Qi; Qi Liu (Environmental Monitoring and Assessment, 2026)

Nitrogen fertilization simultaneously strengthens soil carbon and nitrogen pools, with implications for productivity gain of double-cropping rice system - Junru Li; Yao Liu; Hao Huang; Ning Su; Qiulong Hu; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Biology and Fertility of Soils, 2026)

CRODNet: Cascaded learning network for contactless top-view cattle rotated object detection - Hui Kang; Yuqi Zhang; Longxiang Li; Chunyang Li; Sen Wang; Kai Niu; Yue Rong; Zhiqiang He (Computers and Electronics in Agriculture, 2026)

Microwave-enhanced carbothermal reduction for efficient recovery of valuable metals from spent lithium-ion batteries - Gui-Rong Zhang; Da-Shuai Li; Xing-Yu Huang; Yuan-Long Liu; Yan-Qing Cheng; Ling Tong (Waste Management, 2026)

Millennial rice cultivation shapes depth‑dependent organic carbon mineralization and microbial life strategies in saline paddy soils - Chaoyun Ying; Zhi Ma; Yue Li; Xuechi Rong; Ze Zhang; Guanjun Li; Shuang Wang; Tida Ge; Zhenke Zhu (Soil and Tillage Research, 2026)

Contrasting impacts of wheat rhizosphere and hyphosphere on methane and nitrous oxide emissions under straw incorporation - Baowei Huang; Yongcheng Wu; Zheng-Rong Kan; Fede Berckx; Petra Fransson; Qian Zhang; Feng-Min Li; Martin Weih; Haishui Yang (Soil and Tillage Research, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Lithium ions protected orbital symmetry enables reversible oxygen redox in layered manganese-based cathodes - Ang Gao; Shiguang Zhang; Xiaohui Rong; Qinghua Zhang; Ting Lin; Yichi Wang; Yujie Chen; Valentina A. Bocharova; Weiguang Lin; Shiyu Wang; Pengxiang Ji; Hongwei Li; et al. (Science Bulletin, 2026)

Hydroclimate forcing and anthropogenic impacts trigger an early (∼1650 cal yr BP) regime shift in Chenghai Lake (China) - Qian Wang; John P. Smol; Kathleen M. Rühland; Rong Wang; Xiangdong Yang; Enlou Zhang; Yanjie Zhao; Yanling Li (Quaternary Science Reviews, 2026)

Buckling characteristics of the bucket foundation during installation into silty sand - Haoming Niu; Qing Xu; Mi Zhou; Dingyi Rong; Xihong Zhang; Weiye Lu; Jinhui Li (Ocean Engineering, 2026)

Widespread incongruence in the phylogenomics of the ancient land plant lineage, Selaginellaceae (lycophytes) - Jing Zhao; Hong Yu; Carl J. Rothfels; Jian-Jun Yang; Shao-Li Fang; Zhao-Rong He; Li-Bing Zhang; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2026)

Typhoon-induced cascade effects on hydrological and biogeochemical dynamics in estuary-coast continuum: Insights from multidisciplinary observations and model forecasting in Zhanjiang Bay, China - Huizi Long; Peng Zhang; Jibiao Zhang; Menghan Gao; Binbin Fan; Zhangxi Hu; Zhihao Li; Rong Chen (Journal of Hydrology, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Insights into mechanism of jarosite enhanced vanadium (V) bioreduction by Shewanella oneidensis MR-1 and vanadium immobilization in contaminated soil - Li Zhang; Tao Zhang; Rong Guo; Youbin Si (Journal of Hazardous Materials, 2026)

Quantification and geological implications of manganese, barium, and copper observed by MarSCoDe LIBS at Zhurong landing site on Mars - Yuxuan Luo; Zhaopeng Chen; Jianjun Liu; Yizhong Zhang; Jingjing Zhang; Zhibin Li; Xin Ren; Xiangfeng Liu; Zhenqiang Zhang; Weiming Xu; Guolin Hu; Shaojin Han; et al. (Icarus, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

Remediation of ternary heavy metal-polyethylene microplastics co-contaminated soil using co-modified biochar with deep eutectic solvent and warm patch: competitive interactions, mechanistic insights, and microbial community response - Luxin Zhang; Xiaobing Liu; Sishang Ge; Weiwei Shi; Rui Zhang; Chaoyang Li; Rong Chen (Environmental Research, 2026)

Unsupervised characterization of site conditions from detailed information for improved ground motion modeling - Qingxu Zhao; Mianshui Rong; Yi Ding; Jixin Wang; Bin Zhang; Xiaoshan Kong; Xiaojun Li (Engineering Geology, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

An intelligent nanotheranostic for size-driven integrated tumor radiosensitization and radioprotection - Mengting Gao; Yarong Jin; Xiaorui Song; Jian Zhang; Ajing Wu; Qiao Ye; Binyue Zhang; Jinxuan Li; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Comprehensive review of constructed wetlands implemented with advanced biotechnologies for carbon-neutral treatment of urban wastewater: Enhanced removal of nitrogen and reduction of greenhouse gas emissions - Feifei Jiao; Xuyihui Chen; Tao Zhang; Chengde Sun; Bin Qi; Shichuang Xu; Xuefei Zhou; Yalei Zhang; Yong Hu; Chao Rong; Dapeng Li; Yu-You Li; et al. (Bioresource Technology, 2026)

Investigating the Therapeutic Efficacy of Quality-Controlled, miR-146a-5p-Enriched Small Extracellular Vesicles Derived From MSCs Against Idiopathic Pulmonary Fibrosis - Xin Wang; Lingjiao Meng; Qiuhong Wang; Ruixue Rong; Yu Zhang; Xiaohui Zhao; Chen Liang; Huizhen Guo; Li Deng; Zengqi Tan; Feng Guan; Yi Tan (Stem Cell Reviews and Reports, 2026)
Small extracellular vesicles derived from umbilical cord mesenchymal stem cells (UC-sEvs) may be used for the treatment of idiopathic pulmonary fibrosis (IPF) because of their ability to control inflammation and inhibit fibrosis. However, the lack of clarity regarding the treatment mechanism of IPF and the corresponding quality standards limit the clinical application of these small extracellular vesicles. Here, we established a good manufacturing practice (GMP) grade process for isolating UC-sEvs, and RNA-seq was performed to screen for potential therapeutic cargo in the product to confirm the therapeutic effect of nebulized UC-sEv agents against IPF. Functionally, UC-sEvs inhibited the pulmonary inflammatory response by regulating macrophage function, thereby suppressing the bleomycin toxicity-induced progression of fibrosis. Mechanistically, miR-146a-5p enrichment in UC-sEvs may be involved in alleviating bleomycin-induced IPF by targeting TRAF6/IRAK1 to negatively regulate inflammation. The proposed quality control strategy ensures the stability of the product across three batches, with RNA-seq analysis revealing highly similar miRNA expression profiles. The feasibility of using miR-146a-5p as a key therapeutic molecule has been validated. Finally, on the basis of the results of pharmacodynamics and key therapeutic molecule studies, we provided a detailed quality control standard for IPF therapy by nebulizing UC-sEv. These findings help understand how sEvs impact IPF and the possible consequences of their therapeutic usage and offer a quality standard reference. Graphical Abstract

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Total Saponins of Panax Notoginseng Leaves Modulate the "Microglial-NLRP3/Caspase-1" Axis associated with Gut Microbial/SCFAs Alterations: Correlative Insights into Cognitive Improvement in Senescence - Lan Sun; Jiarong Du; Yuan Xu; Shanshan Wang; Yao Zhang; Rong Yuan; You Lv; Longyan Ding; Yanling Jin; Yu Ren; Xiaoman LV; Jiali Yuan; et al. (Molecular Neurobiology, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Cu–N4 active site sensing platform for point-of-care colorimetric detection of environmental organophosphorus pesticide - Rong Huang; Zhong Dong; Wanyi Zhang; Zhenggang Xue; Dongmei Deng; Wei Wang; Yuanyuan Li; Haibo He; Liqiang Luo (Analytica Chimica Acta, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)